LncRNA H19: a novel player in the regulation of diabetic kidney disease - Wu, Qinrui; Huang, Fengjuan (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD), one of the most severe complications of diabetes mellitus (DM), has received considerable attention owing to its increasing prevalence and contribution to chronic kidney disease (CKD) and end-stage kidney disease (ESRD). However, the use of drugs targeting DKD remains limited. Recent data suggest that long non-coding RNAs (lncRNAs) play a vital role in the development of DKD. The lncRNA H19 is the first imprinted gene, which is expressed in the embryo and down-regulated at birth, and its role in tumors has long been a subject of controversy, however, in recent years, it has received increasing attention in kidney disease. The LncRNA H19 is engaged in the pathological progression of DKD, including glomerulosclerosis and tubulointerstitial fibrosis via the induction of inflammatory responses, apoptosis, ferroptosis, pyroptosis, autophagy, and oxidative damage. In this review, we highlight the most recent research on the molecular mechanism and regulatory forms of lncRNA H19 in DKD, including epigenetic, post-transcriptional, and post-translational regulation, providing a new predictive marker and therapeutic target for the management of DKD.